Therapeutic Potential of Scolopendra subspinipes: A Comprehensive Scoping Review of Its Bioactive Compounds, Preclinical Pharmacology, and Clinical Applications - Ye-Seul Lee; Yoon Jae Lee; In-Hyuk Ha (Toxins)
Scolopendra subspinipes, commonly known as the Chinese red-headed centipede, has been utilized in traditional East Asian medicine for centuries to treat conditions such as chronic pain, inflammation, convulsions, and infections. Recent pharmacological investigations have uncovered a wide array of bioactive molecules—including peptides, alkaloids, and polysaccharide–protein complexes—from both venom and whole-body extracts. This review synthesizes findings from 45 in vitro, in vivo, and clinical studies investigating the pharmacological effects of venom-derived and whole-body-derived compounds from S. subspinipes across multiple domains, including analgesic, anti-inflammatory, antimicrobial, antifungal, antioxidant, antitumor, antithrombotic, anti-fibrotic, and neuroprotective activities, along with a brief scoping review of clinical practice guidelines. Key venom-derived compounds such as the peptide SsmTX-I, immunomodulatory antimicrobial peptide scolopendrasin IX, and antitumor peptide scolopentide exhibit strong mechanistic rationale and preclinical efficacy, positioning them as lead candidates for clinical development. Compounds derived from whole-body extracts, including alkaloids and polysaccharide–protein complexes, also demonstrate promising therapeutic potential. Mechanistic studies suggest these compounds operate via distinct pathways—such as ion-channel inhibition, NF-κB suppression, and apoptosis induction—offering potential advantages over existing therapies. However, current evidence remains primarily preclinical, and challenges such as extract variability, immunogenicity, and lack of standardized dosing must be addressed. Future research should prioritize isolation and structural optimization of key peptides, standardized formulation development, toxicological profiling, and early-phase human trials. The integration of traditional knowledge and modern pharmacological insights underscores the potential of venom- and whole-body-derived S. subspinipes agents to enrich the drug discovery, particularly for conditions with unmet therapeutic needs.